Peran Perangkat Desa Dalam Hal Penyelesaian Sengketa Keperdataan Di Negeri Rumahkay Kecamatan Amalatu Kabupaten Seram Bagian Barat - Wijaya Natalia Panjaitan (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: Civil dispute resolution at the village level is important for maintaining peace and justice in local communities. Village officials, as representatives of local government, play a central role in addressing the civil issues of village communities.Purposes of Devotion: To provide understanding and knowledge to the community, especially the importance of the role of village officials in resolving community disputes. Method of Devotion: The devotion method used is the counseling and mentoring method for the Negeri Rumahkay Community, especially in providing knowledge of the importance of the role of village officials in resolving disputes between communities.Results of the Devotion: Village apparatuses serve a vital role in securing peace and justice in the village community through their efforts in resolving civil disputes through various means of out-of-court dispute resolution.